2012
DOI: 10.3390/biology1030857
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural Gradients to Infer a Potential Response to Climate Change: An Example on the Reproductive Performance of Dactylis Glomerata L.

Abstract: An understanding of the climate conditions governing spatial variation in the reproductive performance of plants can provide important information about the factors characterizing plant community structure, especially in the context of climate change. This study focuses on the effect of climate on the sexual reproductive output of Dactylis glomerata L., a perennial grass species widely distributed throughout temperate regions. An indirect space-for-time substitution procedure was used. Sixty mountain populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Up until now, hierarchical partitioning has been predominantly applied to single models (also called global models because they include all hypothesized explanatory variables; for example in Murray & Conner ; Dainese ). We term the independent effect estimated for j ‐th explanatory variable ( x j ) of the global model Iglobalfalse(xjfalse).…”
Section: Methodsmentioning
confidence: 99%
“…Up until now, hierarchical partitioning has been predominantly applied to single models (also called global models because they include all hypothesized explanatory variables; for example in Murray & Conner ; Dainese ). We term the independent effect estimated for j ‐th explanatory variable ( x j ) of the global model Iglobalfalse(xjfalse).…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, observations should be made over decades, which is rarely possible. Elevation gradients are a powerful tool for testing ecological responses of biota to geophysical influences such as temperature [4], and the influence of changing environment experienced along such gradients has been suggested as analogous to climate warming [5,6]. Hodkinson [6] provided a series of examples where parasitism was measured along elevation gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Some predictions of biotic responses to climate rely on envelope models (Pearson and Dawson 2003). While substantial work and debate focuses on bioclimate envelope modeling to predict species distributions (Busby 1991;Pearson and Dawson 2003;Elith and Leathwick 2009;Dainese 2012), few studies explore the issue of compositional responses of ecosystems to climate change, particularly at the floristic level (Baselga and Araújo 2009; Pucko et al 2011;Friggens et al 2012). Halpin (1997) showed that when the envelope of climatic conditions describing the distribution of an ecosystem no longer exists at a location, the ecosystem contracts and eventually disappears.…”
Section: Introductionmentioning
confidence: 99%